127k views
1 vote
Given y = (2x + 3)2, choose the standard form of the given quadratic equation. 0 = 25x2 0 = 4x2 + 9 0 = 4x2 + 10x + 6 0 = 4x2 + 12x + 9

2 Answers

4 votes

Answer:


4x^2+12x+9

Step-by-step explanation:

We are given that


y=(2x+3)^2

We have to choose standard form of given quadratic equation.

We know that


(a+b)^2=a^2+b^2+2ab

Using this identity


(2x+3)^2=4x^2+9+2* 2x* 3


(2x+3)^2=4x^2+9+12x

Hence, the standard form of given quadratic equation is given by


y=(2x+3)^2=4x^2+12x+9

User RithwikBojja
by
5.4k points
4 votes

Answer:
y=4x^2+12x+9

Step-by-step explanation:

Given quadratic equation :
y = (2x + 3)^2

Using identity :


(a+b)^2=a^2+b^2+2ab

Put
a=2x and
b=3 , then we have


(2x + 3)^2=(2x)^2+(3)^2+2(2x)(3)


\Rightarrow\ (2x+3)^2=4x^2+12x+9

Hence, the standard form of the given quadratic equation
y = (2x + 3)^2 will be :-


y=4x^2+12x+9

User NoCommandLine
by
5.5k points